(untitled) (Diametros, 2015)
There is a special need for solidarity at the global level to address global health disparities. Ter Meulen argues that solidarity must complement justice, and is, in fact, more fundamental than justice to the arrangement of health care practices. We argue that PG/SHG, though a theory of justice, is fundamentally synergistic with solidarity. We relate PG/SHG to Jodi Dean’s conceptual work on reflective solidarity, contrasted with conventional solidarity, as an approach to transnational solidarity that dovetails with PG/SHG. We argue that PG/SHG meets both the need for solidarity at the global level and the need for solidarity within theories of the arrangement of health care practices.